Perioperative sleep disturbance - Min Zhang; Xiafei Lin; Wei Gao; Yufei Ren; Daojie Wang; Dongchen Wu; Duozhi Wu; Zhihua Wang; Guanwen Lin (Medicine, 2026)
Background: Perioperative sleep disturbance is increasingly recognized as a clinically significant issue that may compromise postoperative recovery. Despite its clinical importance, this field lacks a comprehensive bibliometric analysis. This study investigated research trends to guide future work and ultimately enhance perioperative sleep management and patient recovery outcomes. Methods: Records on perioperative sleep disturbance with publication dates between January 1, 2004, and December 31, 2024, were retrieved from Web of Science (WoS) and PubMed. After merging, deduplication, title/abstract screening, and date filtering, 3178 records were retained for bibliometric analysis. Descriptive analyses were based on the full 3178-record dataset, whereas total global citation score/total local citation score and WoS citation-network analyses were based on the 2628 records imported into the WoS-compatible native software workflow. Bibliometric mapping was conducted using Microsoft Office Excel 2024, HistCite, VOSviewer, CiteSpace, Scimago Graphica, and R-bibliometrix/biblioshiny. Results: The analysis included 3178 publications. Annual output increased from 42 publications in 2004 to 441 in 2024, and cumulative output reached 3178 publications by 2024. China (847) and the United States (688) were the most productive countries/regions, while the United States had the highest total global citation score (21,283). The University of California System (82) and the University of Copenhagen (68) were the most productive institutions. Li Y (31) ranked 1st among productive authors, and Buysse DJ (1989) was the most frequently co-cited reference. BMC Anesthesiology and the journal Medicine each published 37 articles, whereas Sleep was the most frequently co-cited journal. The main keywords included surgery, melatonin, quality of life, pain, sleep, and sleep quality. Conclusions: This study systematically mapped research on perioperative sleep disturbance from 2004 to 2024. The field has expanded substantially, with China and the United States contributing the largest body of publications, and the United States showing the strongest citation influence. Current hotspots focus on surgery-related sleep problems, pain, sleep quality, melatonin, quality of life, and postoperative delirium. Future studies should strengthen international collaboration, improve standardized sleep assessment, and evaluate mechanism-based perioperative sleep interventions.